An Ardl Approach to Identify Bank Landing Channel in Indonesia - Akhsyim Afandi (Economic Journal of Emerging Markets, 2009)
This paper tests whether the bank lending channel works in Indonesia. It develops an errorcorrection representation of the Autoregressive Distributed Lag (ARDL) model of two bankcredit markets. Each model takes account of one structural break associated with the 1998financial crisis. The date of the crisis is determined by a unit root test that includes twostructural breaks. Instead of Johansen’s cointegrating procedure, bounds test procedure isimplemented. The estimated error correction model for both markets suggests that bankloans adjust more strongly towards loan supply, implying that monetary-induced disturbancesin bank loans originate from the supply side.Keywords: bank lending channel, unit root, structural breaks